Fernald State School: Sandra Marlow's interview with school matron Ma Bell, side 2 - Marlow, Sandra Kane (Tufts Archival Research Center, 2019)
This is the second part of Sandra Marlow's interview with "Ma Bell," who worked at the Fernald State School. At the time of the interview, she was the last living matron that had worked at the school. The CD was labeled: Fernald State School Sunny Marlow interview; Ma Bell retired matron at the school #2; May Bell side 2.